Transcriptome Analysis of Ovary Development in Nile Tilapia Under Different Photoperiod Regimes - Tang, Zhanyang; Zhou, Yi; Xiao, Jun; Zhong, Huan; Miao, Weiwei; Guo, Zhongbao; Zhang, Xu; Zhou, Lei; Luo, Yongju (Frontiers in Genetics, 2019)
This study investigated the molecular mechanisms involved in ovarian transcriptomic responses in the Nile tilapia over different photoperiods. Histological analysis indicated that ovarian development was significantly different depending on the photoperiod. The photoperiods tested were as follows: LD (12 h light: 12 h dark), LL (24 h light:0 h dark) and DD (0 h light: 24 h dark). These studies showed that a longer photoperiod induced ovary development. Next, ovary transcriptome levels in Nile tilapia over the three photoperiods were sequenced and analyzed. These data indicated that 988, 992 and 1,036 differentially expressed genes (DEGs) were detected by comparing LD–LL, LD–DD, and LL–DD photoperiods. Results from these comparisons detected a number of genes that may be involved in photoperiod-specific regulation of ovarian development. These data provide new insight into the light-induced molecular mechanisms in ovarian development in Nile tilapia.